Insulation of high-storey residential buildings in the territory of urban communities and determination of its energy-environmental efficiency - Moniuk, Iryna (Technology audit and production reserves, 2023)
The object of research is the «boiler plant – heat consumers – environment» system, which is caused, in particular, by high fuel consumption by city boilers serving high-rise residential buildings, including a significant number of buildings of an outdated housing stock, which are characterized by a low level of energy saving. One of the most problematic areas is the increase in emissions of pollutants and greenhouse gases into the atmosphere by boiler units and other power plants, especially during the heating season. In the course of the research, an assessment and analysis of the level of pollution of the city’s atmosphere by emissions from boiler plants, taking into account background pollution, and an analysis of the normative calculation method for determining emissions of pollutants into the atmosphere from power plants were used. The theoretical justification of the method of operational determination of current emissions of urban boiler houses and indicators of their energy-ecological efficiency based on current daily fuel consumption recorded during the entire heating season is also given, with a simultaneous assessment of the energy efficiency of fuel use and the degree of ecological hazard of emissions. The essence of the method is to use the indicator (energy-ecological index) introduced by the authors – K. This indicator simultaneously characterizes the multiplicity of exceeding both the current fuel consumption and the corresponding current emissions of pollutants by the boiler room, relative to their reference (reference) values determined once at the beginning of the heating season at an ambient air temperature of about 8 °C. The proposed temperature method for determining the K index before and after the implementation of both resource-saving technologies and technologies for protecting the atmosphere from emissions in the «boiler plant – heat consumers – environment» system allows to evaluate their effectiveness by the level of reduction in the value of the index, compared to its previous value, that is, to implementation obtained under similar conditions. It has been proven that in order to obtain a tangible energy-ecological effect at the level of a large city from its technology of warming the walls of buildings, its mass centralized implementation is necessary, both for individual high-rise buildings and on the scale of existing residential neighborhoods. For the reconstruction of existing facades, it is proposed to use current industrial technologies for warming the walls of buildings, which are used in new buildings, which are based on the use of mineral wool, in particular ISOVER-plaster. Insulation of walls with ISOVER-plaster will have the following advantages compared to foam plastic: thermal conductivity coefficient – 0.034 W/m·K, against 0.048 W/m·K for foam plastic. When using plates with a thickness of 100 mm ISOVER-plaster is expected to reduce heat loss to approximately 2.8 %, against 2.17 % obtained for foam plastic, which will provide a correspondingly greater energy and ecological effect.